Surface antigen expression on Plasmodium falciparum-infected erythrocytes is modified in alpha- and beta-thalassemia. - Luzzi, G; Merry, A; Newbold, C; Marsh, K; Pasvol, G; Weatherall, D (1991)
In an attempt to determine the mechanism whereby thalassemia in its milder forms may protect against malaria, we have examined the expression of neoantigen at the surface of Plasmodium falciparum-parasitized thalassemic red cells. Neoantigen expression was estimated by measurement of antibody bound after incubation in serum from adults living in a malaria-endemic area, using a quantitative radiometric antiglobulin assay. We found that P. falciparum-parasitized alpha- and beta-thalassemic red cells bind greater levels of antibody from endemic serum than controls: mean binding ratios (+/- SE), respectively, for alpha- and beta-thalassemia compared with controls were 1.69 +/- 0.12 and 1.23 +/- 0.06 on a cell for cell basis, and 1.97 +/- 0.11 and 1.47 +/- 0.08 after a correction for surface area differences. Binding of antibody increased exponentially during parasite maturation. In addition, we found a small but significant degree of binding of naturally occurring antibody to parasitized red cells, the extent of which was also greater in thalassemia. The apparent protective effect of thalassemia against malaria may be related to enhanced immune recognition and hence clearance of parasitized erythrocytes.